Literature review of tai chi in asthma - Dwi Harianto; Iman Permana (STIKES Insan Cendekia Medika Jombang, 2019)
Introduction : Asthma is a condition where a person experiences symptoms of shortness of breath, wheezing, narrow chest. This condition is very disturbing if not immediately addressed. There are those who use medical drugs to handle it, and there are also those who use complementary medicine. That's why here researchers are researching the complementary method journal. Objective : This research aims to analyze the effects of Tai Chi for asthma Method : Using a literature review, this research found 25 research articles which were met the inclusion criterias based on the theme. The articles take from search engines such as: ebsco, proquest, google scholar, and sciencedirect using some keywords such as “Thai Chi exercise”OR “exercise”OR “ breathing exercises”AND “asthma management”. Results : This research found that the effects of Tai Chi to asthma were 4, namely improving the quality of life of patients, reducing recurrence of asthma, improving physical activity and decreasing asma’s symptom Conclusion : Tai Chi are highly recommended to be used as complementary therapy, duet to the possitive impact resulted.